Pendampingan Pengukuran Arah Kiblat Bagi Jama’ah Masjid Al-Muhajirrin Kampung Naramben, Arso XIII, Kabupaten Kerom-Papua - Rahman, Hendra Yulia; Amri, Amri (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: This community service activity is carried out on the basis of the companion because there are still pros and cons to the direction of the Qibla of Al-Muhajirin Mosque in Naramben Village. and the need for public knowledge about the direction of Qibla should be conveyed in the Jamaat. Methodology: In this community assistance using the P3 stage (Planning, Learning, and Mentoring). So this mentoring process will gather service partners in this case Takmir and Jama’ah Masjid Al-Muhajirin Kampung Naramben Arso XIII in guiding and accompanying them with some time until they understand the correct direction of Qibla at the mosque. Results: The results produced in community service activities are to make conflicts of different directions of the qibla by the Al-Muhajirin Mosque congregation resolved. Because after providing material about the direction of the qibla and direct assistance was carried out to measure the direction of the qibla of the al-Muhajirin mosque, the mosque worshippers understood the difference in the direction of the qibla and the position of the right qibla direction at the Al-Muhajirrin Mosque in Naramben Arso-XIII Village. Limitations: The limitation of this activity is that the implementation is not attended by all Al-Muhajirin Mosque congregations in Naramben Village. Then the limitations of technological tools to measure the direction of the Mosque's Qibla are also limitations in this community service activity. Countribution: The contribution in this activity is to help Muslims in understanding the direction of Qibla which is good and correct. So that someone who wants to learn Islam is not only in one particular field, but as a whole. This activity also helps the Al-Muhajirin Mosque Jamaat who still lacks knowledge about the direction of Qibla, will change himself to understand it.